History of the Ukrainian State Formation (Prior to the USSR Breakup) - S. S. Zhiltsov (Проблемы постсоветского пространства)
The changeover of the ruling of the modern Ukrainian territory between East and West had lasted for around 800 years beginning from the Mongol-Tatar invasion. It was that time when Batu Khan defeated Ancient Rus that the present territory of Ukraine came under complete and absolute ruling of the Tatar East. In the 16th century as a part of Lithuania Ukraine was included into the Polish-Lithuanian Commonwealth and then passed under the rule of the Polish magnates, under the yoke of the Western Polish civilization. In 1569 the Union of Lublin was signed that formalized the accession of the Ukrainian territory to the Polish-Lithuanian Commonwealth. In the period from the 10th to the 19th centuries there was no such state as Ukraine on the world political map. In the 10th century some part of the territory of present Ukraine was taken by Kievan Rus, in the 13th century — by Golden Horde, in the 14th-15th centuries — by Lithuania, Golden Horde and Russia. In the next centuries the territory of Ukraine was controlled by the Ottoman Empire, Poland and Russia. And only in 1918 the state of Ukraine appeared on the political map.Single Soviet Ukraine created by Bolsheviks did not present any internal cultural and language unity as it was always shared by different empires being the hostile and irreconcilable centers of force in Europe — the Polish-Lithuanian Commonwealth, Russian Empire and Austro-Hungarian Empire.In 1917-1920 about dozens of different republics were established in the territory of Ukraine. They were isolated within the borders of their formations. Accordingly, it may be said that in 1917-1920 Ukraine presented a mosaic of different formations which were often formed due to ambitions of some scoundrels and political adventurers striving to get to power and to become the leader of a state. But only the tough policy of Bolsheviks aimed to prevent the disintegration process permitted Ukraine to preserve its territory. After its election the Supreme Council started preparation of the Draft Declaration of Ukraine State Sovereignty simultaneously with the Draft Law on Ukraine State Sovereignty. Both drafts were considered in May 1990. After their discussion it was decided to develop the Draft Declaration of State Sovereignty.On July 16, 1990 the Ukrainian Parliament after long discussions adopted the Declaration on State Sovereignty of Ukraine by majority voting. This declaration which did not change and substitute the Constitution of Ukrainian SSR became a very important document for establishment of the Ukrainian statehood having laid the basis for the future Constitution of Ukraine.The concept of the new Constitution of Ukraine envisaged the establishment of the presidential republic. As a result, in June 1991 the laws «On Establishment of the Office of President of Ukrainian SSR with Making Alterations and Additions in the Constitution», «On President of Ukrainian SSR” and “On Election of President of Ukrainian SSR». The office of president was established to strengthen the vertical of executive power and to make it in the future independent of executive power of union bodies. The law assigned broad authorities to the president. Thus, the president acquired the right to cancel the decisions of the USSR bodies of executive power in the territory of Ukrainian SSR if they contradicted its constitution.By mid-1991 the legislative base was created in Ukraine which, in fact, made it an independent state as the laws adopted in 1990 and in the first half of 1991 brought out Ukraine from subordination to the USSR powers. The single economic, political and military space of the USSR practically ceased to exist. By this time Ukraine subordinated only nominally to union authorities. On August 24 the Extraordinary Meeting of Supreme Rada passed the Act on Declaration of Independence of Ukraine. That time it was also decided to conduct on December 01 the republican referendum to confirm the Act of Independence. This was done with a view to demonstrate to the union authorities that the Ukrainian people were endeavoring to become independent, thus, making legitimate the Act of Independence. After becoming independent in 1991 Ukraine entered the new stage of its development. The regional system of Ukraine revealed two clear poles — Donbass and Galichina which determined the country’s development for decades ahead.